The Influence of the Means Ends Analysis (MEA) Learning Model on Students’ Critical Thinking Ability on Fraction Topic - Fauzah, Zafira; Wafiqoh, Risnina; Hevitria, Hevitria (Pelangi (e-Journal), 2023)
This research is driven by the low of student’s critical thinking ability in learning Mathematics as well as teachers that still use conventional models during teaching and learning activities. This research aims to determine the effect of the Means Ends Analysis (MEA) learning model on students' critical thinking ability. The quasi-experimental method is used in this research along with a quantitative approach. The research design uses a non-equivalent control group pre-test post-test design. This research applied the MEA learning model to the experimental class and the conventional model to the control class. The population in this study was the fifth-grade students at one of the Pangkalpinang State Elementary Schools. Purposive sampling is used as the sampling technique. The samples in this research were Class V-A as the experimental and Class V-B as the control class. The data collection technique uses a critical thinking ability test in the form of essay questions consisting of a pre-test and a post-test. The data analysis technique in this research uses the normality test (Kolmogorov Smirnov test), homogeneity test (Fisher test), and hypothesis test which uses the dependent sample t-test (pooled variance). Based on the results of the hypothesis test using the dependent sample t-test (pooled variance), the value of tcount = 5,185 > ttable = 1,995. So, it can be concluded that Ha is accepted; it means that there is an influence of the MEA learning model on students' critical thinking ability in class V on fraction topic.